TNF-α/TNF-R System May Represent a Crucial Mediator of Proliferative Synovitis in Hemophilia A - Manetti, Mirko (J Clin Med, 2019)
Hemophilic arthropathy (HA) typically begins with proliferative synovitis that shares some similarities with inflammatory arthritides, in which the proinflammatory cytokine tumor necrosis factor (TNF)-α has a crucial pathogenetic role. Inappropriate release of TNF-α was shown to contribute to arthropathy development following intra-articular bleeding in hemophilic mice. Here, we were interested in determining whether systemic levels of TNF-α and synovial tissue expression of the TNF-α/TNF receptor (TNF-R) system could be increased and related to joint damage in hemophilia A patients with severe HA. Serum levels of TNF-α measured by quantitative enzyme-linked immunosorbent assay (ELISA) were significantly increased in HA patients (n = 67) compared to healthy controls (n = 20). In HA patients, elevated TNF-α levels were significantly associated with the number of hemarthroses, the grade of synovial hypertrophy, and both the clinical World Federation of Hemophilia score and ultrasound score. The expression of TNF-α, TNF-R1, and TNF-R2 was strongly increased in HA synovium (n = 10) compared to the non-inflamed osteoarthritis control synovium (n = 8), as assessed by both immunohistochemistry and Western blotting. Increased protein levels of TNF-α, TNF-R1, and TNF-R2 were retained in vitro by HA fibroblast-like synoviocytes (n = 6) with respect to osteoarthritis control fibroblast-like synoviocytes (n = 6). Stimulation with TNF-α resulted in a significant increase in HA fibroblast-like synoviocyte proliferation quantified by the water-soluble tetrazolium (WST)-1 assay, while it had no relevant effect on osteoarthritis fibroblast-like synoviocytes. Quantification of active/cleaved caspase-3 by ELISA demonstrated that TNF-α did not induce apoptosis either in HA or in osteoarthritis fibroblast-like synoviocytes. The TNF-α/TNF-R system may represent a crucial mediator of proliferative synovitis and, therefore, a new attractive target for the prevention and treatment of joint damage in HA patients. Our findings provide the groundwork for further clinical investigation of anti-TNF-α therapeutic feasibility in hemophiliacs.